Efektivitas Penggunaan Model Window Shopping untuk Meningkatkan Minat Siswa Mengikuti Layanan Bimbingan dan Konseling - Muh. Mansyur Thalib; Nur Eka Wahyuningsih; Dian Fitriani; Nurwahyuni Nurwahyuni; Hasan Hasan (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
The main objective of this research is to increase students' interest in following the guidance service by using the window shopping model in classical guidance services. The type of research used is quasi-experimental. The number of subjects in this study was 29 students. Data collection was carried out using a questionnaire. The data collected was then analyzed descriptively and inferentially. The results showed that before the window shopping model was used, students' interest in participating in the guidance service varied from not interested to interested. Still, the most dominant classification was less interested and not interested. After using the window shopping model, students' interest in participating in classical guidance services also varied, but the most dominant was the classification of moderately interested and interested. This study's results indicate an increase in students' interest in following classical guidance services. Therefore, it can be concluded that the use of the window shopping model in implementing guidance services effectively increases student interest in participating in guidance services. The results of this study imply that school counselors can follow up using a window shopping model in implementing classical guidance services. School counselors can also use this model in guidance and counseling action research as an effort for continuous professional development.